O luto na clínica com afásicos - Cordeiro, Michelly Daiane de Souza Gaspar (2019)
In the clinical work with aphasics the speech-language pathologist confronts a patient about the effect of a before and after neurological event, and therefore suffering with a new linguistic condition. The mourning for the loss of a position in the language is experienced and has effects in the speech-language therapy. The assumption that I raised to work and to deepen in this thesis is related to the mourning by the loss that aphasia establishes - which has effects in the treatment. The subjective drama instituted by aphasia (FONSECA, 2002) is a theoretical issue articulated to the mourning that deserves refinement. Thus, this thesis had a theoretical character, with a vast bibliographical revision that went through the concept of mourning and melancholy in psychoanalysis, and provided a theoretical displacement from reading operators that yielded to understand the mourning in aphasia under the bias of the Clinic of Language. The entanglement of mourning with subjective drama is related to the narcissistic wound that the aphasic picture produces. The dry loss that aphasia establishes does not offer a possibility of compensation, the elaboration will be from a crossing that summons the Symbolic, Imaginary and Real registers, this offers new possibilities to deal with the loss and to face the new linguistic condition. Although it was not the central objective to discuss about the practice, it was observed that autobiographical reports can be chosen as clinical devices to subsidize this clinical course of the patient. It is hoped that this thesis will contribute to future theoretical-practical articulations in the aphasic care setting